2019
DOI: 10.1161/str.50.suppl_1.tp270
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TP270: When Telestroke Programs Work, Bed Size Really Doesn’t Matter

Abstract: Background: Telestroke rural networks are comprised of micro>small>medium>large sized hospitals without specialized neurology support. Many times the micro hospitals are < 25 beds. In an examination of spoke hospitals in the Arkansas Stroke Assistance through Virtual Emergency Support (AR SAVES) telestroke program, we determined program efficacy correlating bed number. Efficacy was determined by the mean Door-to-ED physician (D2MD) time and door-to-needle (D2N) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that telestroke facilitated administration of tPA to patients in community hospitals and rural hospitals (as small as 100 beds or less) has outcomes comparable to those of in-person treatment at comprehensive stroke care centers [58][59][60][61]. Even with in a stroke network, the performance of spoke sites is similar regardless of the bedsize [62]. Also, the use of telestroke at rural hospitals can provide patients with comparable or reduced time between symptom onset and tPA administration [door-to-needle time (DTN)] compared to those directly presenting to tertiary care centers [63].…”
Section: Effectiveness and Utility Of Telestroke In Management Of Acumentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that telestroke facilitated administration of tPA to patients in community hospitals and rural hospitals (as small as 100 beds or less) has outcomes comparable to those of in-person treatment at comprehensive stroke care centers [58][59][60][61]. Even with in a stroke network, the performance of spoke sites is similar regardless of the bedsize [62]. Also, the use of telestroke at rural hospitals can provide patients with comparable or reduced time between symptom onset and tPA administration [door-to-needle time (DTN)] compared to those directly presenting to tertiary care centers [63].…”
Section: Effectiveness and Utility Of Telestroke In Management Of Acumentioning
confidence: 99%
“…Most of the measures are already being performed with a high compliance rate and innovation. They should be expanded to pre-hospitalization and post-hospitalization settings as well as to telestroke for further improvement of stroke care [62,[96][97][98][99]. Universal guidelines about definitions of times in stroke chain-of-care, protocols for consultant notification, and specific standard stepwise processes that can be applied universally for telestroke networks will be useful in standardizing telestroke models.…”
Section: Quality Measures: Final Thoughtsmentioning
confidence: 99%